An Educational App for the Selection of Blood Glucose Meters: A Cross-Sectional Study - Doniec Rafał; Krzepina Tymoteusz; Siecinski Szymon; Tausif Irshad Muhammad; Grzegorzek Marcin (Current Directions in Biomedical Engineering)
In this cross-sectional study, we examined the abundance of blood glucose meter (BGM) models in the Polish and German medical device markets and their technical specifications. Information from a medical equipment wholesaler’s database was gathered for comparison of BGMs from five manufacturers: Roche Diabetes Care, LifeScan Inc, Abbott, Ascensia Diabetes Care, and Genexo, and for model Glucomaxx BT TaiDoc Technology Corporation. Key parameters such as blood sample size, measurement time, memory capacity, and measurement range were considered. An application was developed to aid in BGM selection for people with type 1 or type 2 diabetes. The results showed a high correlation with laboratory measurements and similarity in key functionalities between the models. The application, tested on 30 individuals aged 18 to 79 years, demonstrated stability, speed, and a user-friendly interface, facilitating efficient data processing and generating recommendations.